Chromatin remodeling: demethylating H3K4me3 of type I IFNs gene by Rbp2 through interacting with Piasy for transcriptional attenuation. Issue 2 (4th January 2018) - Yu, Xiaoli; Chen, Hui; Zuo, Chen; Jin, Xi; Yin, Yibing; Wang, Hong; Jin, Mei; Ozato, Keiko; Xu, Songxiao
Abstract : Type I IFNs (IFNIs) are involved in the course of antiviral and antimicrobial activities; however, robust inductions of these can lead to host immunopathology. We have reported that the Pias (protein inhibitor of activated signal transducer and activator of transcription) family member, Piasy, possesses the ability to suppress IFNI transcriptions in mouse embryonic fibroblasts (MEFs), yet the specific molecular mechanism by which it acts remains elusive. Here, we identify that the H3K4me3 levels, one activation mark of genes, in MEFs that were stimulated by poly(I:C) were impaired by Piasy in the IFN‐β gene. Piasy bound to the promoter region of the IFN‐β gene in MEFs. Meanwhile, retinoblastoma binding protein 2 (Rbp2) was proven to be the only known and novel H3K4me3 demethylase that interacted with Piasy. Overexpression of Rbp2, but not its enzymatically inactive mutant Rbp2 H483G/E485Q, retarded the transcription activities of IFNI, whereas small interfering RNA–mediated or short hairpin RNA–mediated knockdown of Rbp2 enhanced IFNI promoter responses. Above all, coexpression of Piasy and Rbp2 led to statistically less IFNI induction than overexpression of either Piasy or Rbp2 alone. Mechanistically, Piasy bound to the Jmjc domain (451–503 aa) of Rbp2 via its PINIT domain (101–218 aa), which is consistent with the domain required for their attenuation of transcription and H3K4me3 levels of IFNI genes. Our study demonstrates that Piasy may prevent exaggerated transcription of IFNI by Rbp2‐mediated demethylation of H3K4me3 of IFNI, avoiding excessive immune responses.—Yu, X., Chen, H., Zuo, C., Jin, X., Yin, Y., Wang, H., Jin, M., Ozato, K., Xu, S. Chromatin remodeling: demethylating H3K4me3 of type I IFNs gene by Rbp2 through interacting with Piasy for transcriptional attenuation. FASEB J. 32, 552–567 (2018). www.fasebj.org